1961
DOI: 10.1121/1.1936887
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Repetition of a Continuous Flow of Words

Abstract: This study was designed to evaluate the effect of rate (68, 127, 180 words/min) and intensity (20, 40, 60 SRT) of stimulus presentation, and of practice, upon concurrent repetition of a continuous flow of heard words. Subjects were 33 enlisted men. A three-part tape was made to obtain an SRT, to present a pretest trial, and to present three PB-50 lists read as continuous speech. Intelligibility scores were assigned to each subject's taped repetitions. Twelve subjects had an 8-day practice with other PB lists. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For decades there has been discrepancies regarding the naturalness and intelligibility of shadowed speech. Some research has suggested that shadowed speech is distorted and unnatural (Cherry, 1953;Wingate, 1976;Sergeant, 1961), while others have reported shadowed speech as clearly intelligible and containing prosodic contour (Chistovich, Aliakrinskii & Abulian, 1960;Marslen-Wilson, 1985;Schwitzgebel & Taylor, 1980). Cherry (1953) reported that participants found shadowing surprisingly easy; however, there were apparent effects of the task on the naturalness of the subsequent speech output.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades there has been discrepancies regarding the naturalness and intelligibility of shadowed speech. Some research has suggested that shadowed speech is distorted and unnatural (Cherry, 1953;Wingate, 1976;Sergeant, 1961), while others have reported shadowed speech as clearly intelligible and containing prosodic contour (Chistovich, Aliakrinskii & Abulian, 1960;Marslen-Wilson, 1985;Schwitzgebel & Taylor, 1980). Cherry (1953) reported that participants found shadowing surprisingly easy; however, there were apparent effects of the task on the naturalness of the subsequent speech output.…”
Section: Introductionmentioning
confidence: 99%
“…Cherry (1953, p. 978) asserted that one noticeable characteristic of shadowed speech was its monotony and described shadowed speech as having "…very little emotional content or stressing of the words…" Wingate (1976) reported that shadowed speech is often described as lacking normal prosody and is poorly articulated. Sergeant (1961) investigated the intelligibility of shadowed speech. Twentyfour participants shadowed prose presented at 115 words per minute (WPM) or less.…”
Section: Introductionmentioning
confidence: 99%
“…One concern with using verbal shadowing as a method of enrollment is whether or not the speech output during shadowing would be natural and intelligible enough to be effective as an enrollment method. For example, some research has suggested that shadowed speech is distorted and unnatural (Cherry, 1953;Wingate, 1976;Sergeant, 1961), while others report shadowed speech as clearly intelligible and containing prosodic contour (Chistovich, Aliakrinskii & Abulian, 1960;Marslen-Wilson, 1985;Schwitzgebel & Taylor, 1980).…”
Section: Introductionmentioning
confidence: 99%